Chemo-dynamical substructure in the M31 inner halo globular clusters: further evidence for a recent accretion event. Issue 4 (30th November 2022) - Lewis, Geraint F; Brewer, Brendon J; Mackey, Dougal; Ferguson, Annette M N; Li, Yuan (Cher); Adams, Tim
ABSTRACT: Based upon a metallicity selection, we identify a significant subpopulation of the inner halo globular clusters in the Andromeda Galaxy, which we name the Dulais Structure. It is distinguished as a co-rotating group of 10–20 globular clusters that appear to be kinematically distinct from, and on average more metal-poor than, the majority of the inner halo population. Intriguingly, the orbital axis of this Dulais Structure is closely aligned with that of the younger accretion event recently identified using a subpopulation of globular clusters in the outer halo of Andromeda, and this is strongly suggestive of a causal relationship between the two. If this connection is confirmed, a natural explanation for the kinematics of the globular clusters in the Dulais Structure is that they trace the accretion of a substantial progenitor (∼10 11 M⊙ ) into the halo of Andromeda during the last few billion years, which may have occurred as part of a larger group infall.